Financial Frictions, Product Quality, and International Trade - Rosario Crinò; Laura Ogliari (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2015)
An influential literature shows that product quality varies widely across countries and industries. In this paper, we propose and test an explanation that rests on the interplay between cross-country differences in financial frictions and cross-industry differences in financial vulnerability. We organize the empirical analysis around a simple trade model with heterogeneous firms, endogenous output quality, country heterogeneity in financial frictions, and industry heterogeneity in financial vulnerability. We estimate the model using a unique data set, which contains estimates of export quality, measures of financial development, and indicators of financial vulnerability for all manufacturing industries and countries in the world over the last three decades. We find the interplay between financial frictions and financial vulnerability to be a first-order determinant of the observed variation in product quality across countries and industries. We also show that quality adjustments are a key mechanism through which financial development affects aggregate trade flows and shapes the industrial composition of countries exports.
Keywords: F14; F36; G20; 330; Financial Imperfections; Product Quality; Trade Flows